The Sox10Dom Mouse: Modeling the Genetic Variation of Waardenburg-Shah (WS4) Syndrome - Southard-Smith, E. Michelle; Angrist, Misha; Ellison, Jane S.; Agarwala, Richa; Baxevanis, Andreas D.; Chakravarti, Aravinda; Pavan, William J. (Genome Research, 1999)
Hirschsprung disease (HSCR) is a multigenic neurocristopathy clinically recognized by aganglionosis of the distal gastrointestinal tract. Patients presenting with aganglionosis in association with hypopigmentation are classified as Waardenburg syndrome type 4 (Waardenburg-Shah, WS4). Variability in the disease phenotype of WS4 patients with equivalent mutations suggests the influence of genetic modifier loci in this disorder. Sox10Dom /+ mice exhibit variability of aganglionosis and hypopigmentation influenced by genetic background similar to that observed in WS4 patients. We have constructed Sox10Dom /+ congenic lines to segregate loci that modify the neural crest defects in these mice. Consistent with previous studies, increased lethality ofSox10Dom /+ animals resulted from a C57BL/6J locus(i). However, we also observed an increase in hypopigmentation in conjunction with a C3HeB/FeJLe-a/a locus(i). Linkage analysis localized a hypopigmentation modifier of the Dom phenotype to mouse chromosome 10 in close proximity to a previously reported modifier of hypopigmentation for the endothelin receptor B mouse model of WS4. To evaluate further the role of SOX10 in development and disease, we have performed comparative genomic analyses. An essential role for this gene in neural crest development is supported by zoo blot hybridizations that reveal extensive conservation throughout vertebrate evolution and by similar Northern blot expression profiles between mouse and man. Comparative sequence analysis of the mouse and humanSOX10 gene have defined the exon–intron boundaries ofSOX10 and facilitated mutation analysis leading to the identification of two new SOX10 mutations in individuals with WS4. Structural analysis of the HMG DNA-binding domain was performed to evaluate the effect of human mutations in this region.